Relationships between school climate, bullying and delinquent behaviours - Aldridge, Jill; McChesney, Katrina; Afari, Ernest (Springer, 2017)
© 2017 Springer Science+Business Media B.V. Given that schools are, potentially, powerful sites for influencing adolescent behaviour, it is important that there is greater understanding of the psychosocial aspects of the school climate that can be leveraged for this purpose. The research reported in this article used structural equation modelling (with data from a sample of 6120 students at Australian high schools) to examine the influence of the psychosocial school-level environment on students’ self-reported experiences of bully victimisation (i.e. being victims of bullying) and engagement in delinquent behaviours. Further, we examined whether bully victimisation mediated the relationships between school climate variables and delinquent behaviours. School connectedness and rule clarity were negatively associated with both bully victimisation and delinquency (p < 0.05), and teacher support was negatively associated with bully victimisation (p < 0.01), confirming the importance of these aspects of the school-level environment. However, affirming diversity and reporting and seeking help both had positive influences on bully victimisation (p < 0.05), raising concerns about the ways in which these aspects of the school-level environment might have been promoted. Importantly, bully victimisation was found to mediate the influence of five of the six school climate constructs on delinquent behaviours (p < 0.001). This study advance our understanding of how specific aspects of the school climate influence the prevalence of bullying and delinquent behaviour, adding weight to the call for educators to actively monitor and enhance psychosocial aspects of the school climate in order to improve student behavioural outcomes.